IMPLEMENTASI PENGEMBANGAN KREATIVITAS MELALUI KEGIATAN EKSTRAKURIKULER DI SD MUHAMMADIYAH BANTUL KOTA YOGYAKARTA (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2021)
To develop students’ creativity, Muhammadiyah elementary school of Bantul City hold some extracurricular activities such as robotic, painting, and Batra machine shop. The purpose of this research was to describe the implementation of the development of creativity through extracurricular activities of robotic, painting and Batra machine shop in Muhammadiyah elementary school of Bantul City. The design of this research was Qualitative with a case study approach. The subject of this study included the school principal, extracurricular coordinator, and the students. Data collection was through interview and documentation. Data validity used triangulation of sources and methods. The data analysis technique used an interactive model of Milles and Huberman. The result of the research showed that extracurricular activities that had been held helped to develop students’ talent according to their potential, develop students’ creativity, and increase self-confidence. The material taught was adjusted to students’ ability. The learning conducted was designed to increase students’ interest, students’ spirit, and ease the student to understand the material delivered. The evaluation was conducted periodically through the evaluation process and evaluation of learning outcomes. The implementation of the program is supported by the school’s facilities and infrastructure, suitable activities management, students’ spirit, motivation from the parents, and a competent coach.